Geospatial analysis of wildfire patterns and temporal trends in Kohat Division, Pakistan, using Remote Sensing and GIS - Iman, Aiman; Rahman, Atta-ur; Rahman, Ghani (Ecological Questions, 2025)
This study analyzes the spatial and temporal patterns of wildfires in the Kohat Division of Pakistan using Landsat satellite imagery from 2013 to 2022. Kohat Division falls in the extension of Hindukush and Sufaid Koh ranges, drained by Kurram and Kohat Toi rivers. The study area is an ecologically diverse region with a variety of tree species. The Normalized Burn Ratio (NBR) index and Delta Normalize Burn Ratio (dNBR) indices were applied to map burnt areas and assess wildfire intensity. The results revealed that wildfire incidents peaked in 2016 and 2020, causing extensive damage in the Kurram and Orakzai districts. Temporal analysis showed an increasing frequency of wildfire associated with higher pre-fire temperature and prolonged dry conditions. The findings highlight the growing vulnerability of forest ecosystems in Pakistan and underline the need for continuous satellite-based monitoring and proactive forest management strategies.